Spiritual Eco-Literacy: Model Pendidikan Agama Islam Untuk Generasi Muda Di Era Krisis Iklim - SAPARUDDIN (Andragogia: Journal Education Science And Islamic Studies, 2025)
The global climate crisis has highlighted the urgency of a transformative pedagogical framework in Islamic Religious Education (IRE/PAI) that goes beyond normative teaching and integrates ecological awareness. This study aims to formulate a model of spiritual ecological literacy as an Islamic education paradigm that integrates values based on taw??d, environmental ethics, and practice-oriented piety to shape an environmentally conscious generation. Using a qualitative approach, this research applies thematic analysis through literature review and in-depth interviews with PAI teachers and boarding school students. Findings indicate that this model effectively fosters an ecologically responsible religious paradigm among students, enhances the integration of environmental values into the PAI curriculum, and transforms pedagogical practices from a dogmatic model to a participatory ecological model. The uniqueness of this study lies in its integration of kauniyah verses, the Islamic principle of ?if? al-bi’ah (environmental preservation), and eco-pedagogical strategies into a systematic and applicable framework for Islamic education. The implications of this model are relevant for curriculum reform, teacher training, and policy-making in Islamic education that is responsive to ecological challenges. This spiritual ecological literacy model significantly contributes to integrating sustainability-based education into the theoretical and practical landscape of contemporary Islamic pedagogy.